Methods and TechniquesStent loss in the radial artery – surgical vs. interventional approach – report of two cases - Baszko, Artur; Telec, Wojciech; Naumowicz, Eryk; Siminiak, Tomasz; Kałmucki, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Stent loss during coronary angioplasty is a complication that can be managed in various manners; however, transradial access limits the options available. We describe two coronary interventions complicated by stent dislodgement, initially managed by pulling the stent back to the radial artery. Both stents were unwillingly lost on different levels in radial arteries. The first case was managed with a direct radial artery cut-down because distal location made it a quick and straightforward procedure. In the second case a partially deployed stent was lost in the proximal part of the radial artery. It was rewired, deployed, and post-dilated with a larger balloon. This enabled continuation of the procedure using the same access. Both cases were asymptomatic during 24 months of follow-up. It is crucial to avoid leaving artificial bodies in arteries supplying vital organs because stent-related thrombosis or stenosis may seriously compromise blood flow. Removing the stent via the introducer sheath should be considered the optimal treatment. Unfortunately, it is common that a partially expanded stent will not pass through the sheath. The superficial location of the distal radial artery segment facilitates surgical cut-down with local anaesthesia. When dislodgement occurs in deeper segments of the radial artery, the benefits from cut-down seem to be less because the procedure might take more time and be more difficult – as in the presented case in which we decided to rewire and fully expand the stent in situ . Retrieval of the stent at all costs might have led to further complications; hence stent deployment may be a good alternative to retrieval in such cases.